Literal Translation as a Pedagogical Strategy in Teaching Qira’ah Texts - Laili Hanifah; Muhammad Nu'man; Syafiul Naqsya Bandiy (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study examines the implementation of the literal translation method in Arabic language learning, specifically in developing reading skills (qirā’ah). The research was motivated by the persistent difficulties students face in comprehending Arabic texts due to limited vocabulary and contextual understanding. The study focused on seventh-grade students at MTsN 2 Sidoarjo, where the ability to interpret Arabic texts begins to be systematically cultivated. The main objective was to describe how the literal translation method is applied in the classroom and to analyze its strengths and weaknesses in enhancing comprehension. Using a qualitative descriptive approach, data were collected through classroom observations and literature review. The findings indicate that the literal translation method effectively supports students in grasping sentence structures and lexical meanings, thus easing access to textual content. Nevertheless, the method has notable limitations, particularly its tendency to overlook contextual and inferential meanings. Therefore, while the literal translation method remains relevant as a foundational strategy in qirā’ah instruction, it should be complemented by contextual and communicative approaches to foster a more holistic understanding among learners.